2008
DOI: 10.3758/mc.36.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Can the survival recall advantage be explained by basic memory processes?

Abstract: Nairne, Thompson, and Pandeirada (2007) demonstrated a striking phenomenon: Words rated for relevance to a grasslands survival scenario were remembered better than identical words encoded under other deep processing conditions. Having replicated this effect using a novel set of words (Experiment 1), we contrasted the schematic processing and evolutionary accounts of the recall advantage (Experiment 2). Inconsistent with the schematic processing account, the grasslands survival scenario produced better recall t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
191
9
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(221 citation statements)
references
References 21 publications
13
191
9
8
Order By: Relevance
“…Although identifying cognitive adaptations is notoriously difficult, it is possible to hypothesise within an evolutionary framework (see, e.g., Klein, Cosmides, Tooby, & Chance, 2002). Accordingly, a growing number of researchers are approaching memory in this way (see Kang, McDermott, & Cohen, 2008;Otgaar, Smeets, & van Bergen, 2010;Weinstein, Bugg, & Roediger, 2008), and the results seem to be consistent with the notion that memory does, at least to some degree, differentially deal with information that is processed according to a survival scenario, as compared to when information is processed in other ways.…”
supporting
confidence: 63%
“…Although identifying cognitive adaptations is notoriously difficult, it is possible to hypothesise within an evolutionary framework (see, e.g., Klein, Cosmides, Tooby, & Chance, 2002). Accordingly, a growing number of researchers are approaching memory in this way (see Kang, McDermott, & Cohen, 2008;Otgaar, Smeets, & van Bergen, 2010;Weinstein, Bugg, & Roediger, 2008), and the results seem to be consistent with the notion that memory does, at least to some degree, differentially deal with information that is processed according to a survival scenario, as compared to when information is processed in other ways.…”
supporting
confidence: 63%
“…Although some studies show that the survival recall advantage remains present even when appropriate control conditions are used (e.g., Nairne et al, 2009;Weinstein et al, 2008), no studies have focused on whether other classes of stimuli (e.g., pictures) would also be affected by survival processing. Our study is the first to demonstrate that the survival recall effect can be elicited when another type of stimuli is used.…”
Section: Resultsmentioning
confidence: 99%
“…In further research, it was found that the survival recall advantage persisted when control conditions were used that equated the survival scenario in terms of arousal, novelty, media exposure (Kang, McDermott, & Cohen, 2008), and schematic processing (Weinstein, Bugg, & Roediger, 2008), but also when scenarios were designed that presumed to tap ancestral priorities, such as hunting and gathering activities (Nairne, Pandeirada, Gregory, & Van Arsdall, 2009). These studies provide compelling evidence that survival processing results in improved retention, yet research into this area remains relatively scarce.…”
mentioning
confidence: 99%
“…For example, Nairne's (2005Nairne's ( , 2010 advocacy of memory as a system evolved to enhance survival (clearly a future-oriented enterprise; e.g., Klein et al, 2011) has resulted in a highly active program of research exploring the effects of encoding conditions (survival versus non-survival) on measures of retention (e.g., Burns, Hwang, & Burns, 2011;Butler, Kang, & Roediger, 2009;Kang, McDermott, & Cohen, 2008;Klein, 2012;Klein, Lax, et al, 2010;Klein, Robertson, et al, 2010, Klein et al, 2011Kroneisen & Erdfelder, 2011;Nairne & Pandeirada, 2008;Nairne, Pandeirada, Gregory, & Van Arsdall, 2009;Otgaar, Smeets, & van Bergen, 2010;Soderstorm & McCabe, 2011;Weinstein, Bugg, & Roediger, 2008; for recent reviews, see Howe & Otgaar, 2013;Klein, in press). Another approach to memory that emphasizes its futureoriented aspects is that of memory in its prospective capacities (for review, see Brandimonte, Einstein, & McDaniel, 1996).…”
Section: Discussionmentioning
confidence: 99%